Sistem Automatic Main Failure Pada Genset Berbasis Outseal PLC - Munir, Kartika; Rohan, Rohan; Misriana, Misriana; Asran, Asran; Yana, Dewi (Teknik Elektro Politeknik Negeri Padang, 2025)
Electrical energy is an important part of supporting life. PLN, as the main source of electricity supply, does not guarantee that it will always be reliable, so alternative resources are needed to support these electricity needs; the resources required to replace PLN's main resource are generators. The automatic main failure is equipment with an automatic control system to overcome main channel disturbances of the electric energy supply system and generator heating system. To extend the genset life in the input section, a push button is a conventional control on the automatic main failure circuit, which includes starting the generator, the generator off, and resetting. In the process section, the Outseal PLC Mega V1 functions as a data or command processor from input to output. From the test, it can be concluded that the time needed to activate the generator when the PLN goes out is ± 15 seconds if the generator can be activated by starting once. The fuel indication system also works according to its function. From the results of the generator heating system scheduled for automatic main failure, the time that has been programmed is 1 time in 7 days for ± 45 minutes